Gendered morality: classical Islamic ethics of the self, family, and society - Ayubi, Zahra (Columbia University Press, 2019)
Epistemology and gender analytics of Islamic ethics -- Gendered metaphysics, perfection, and power of the (hu)man's soul -- Ethics of marriage and the domestic economy -- Homosocial masculinity and societal ethics -- Prolegomenon to feminist philosophy of Islam.